Neurodevelopmental Co morbidities of Poorly-Controlled Childhood Epilepsy: A Case-Control Study (Medicine Today, 2021)
Introduction: The epilepsy associated co morbidities are often underestimated, consequently, undertreated. The aim of the present study was to determine neurodevelopmental co morbidities associated with poorly controlled childhood epilepsy.Materials and Methods: This retrospective study was performed from January 2007 to December 2008 at Paediatric Neurology outpatient department in Bangabandhu Sheikh Mujib Medical University, Dhaka, among the children with epilepsy of 7 months to 15 years age who had history of at least 6 months treatment with rational antiepileptic drugs daily with adequate compliance. There were two groups of patients; group 1, consisted of 50 poorly controlled epilepsy patients and group 2, comprised 50 well-controlled epilepsy patients. We retrospectively reviewed EEGs and medical records from these children. Features of neurolodevelopmental co morbidities were compared between the two groups.Results: In this study, initial EEG was abnormal significantly in poorly controlled group (OR= 5.27; p=0.025). Co morbidities- cerebral palsy, language and speech delay, motor delay, microcephaly and cognitive disability were significantly higher in poorly-controlled epilepsy group compared to well-controlled epilepsy group (60.0% vs. 24.0%, p